Social Planning and Economic Coercion - Beat Hintermann; Thomas F. Rutherford (Center for Economic Studies and ifo Institute (CESifo), 2014)
We develop a theory of social planning with a concern for economic coercion, which we define as the difference between consumers' actual utility, and the counterfactual utility they expect to obtain if they were able to set policy themselves. Reasons to limit economic coercion include protecting minorities, preventing disenfranchised groups from engaging in socially costly behavior, or political economy considerations. As long as consumers are fully rational, limiting coercion is equivalent to placing more welfare weight on coerced consumers at the expense of others. If, however, consumers are not fully rational and/or informed, counterfactual utility becomes endogenous to current policy, and the welfare loss associated with limiting coercion increases. We set up a numerical version of our model and find that the error-related welfare loss can be substantial.
Keywords: D03; D04; H21; H22; H23; H31; H41; 330; coercion; social planning; public finance; counterfactual utility